Gravitation without the equivalence principle - Aldrovandi, R.; Pereira, J. G.; Vu, K. H. (Kluwer Academic/plenum Publ, 2004)
In the general relativistic description of gravitation, geometry replaces the concept of force. This is possible because of the universal character of free fall, and would break down in its absence. on the other hand, the teleparallel version of general relativity is a gauge theory for the translation group and, as such, describes the gravitational interaction by a force similar to the Lorentz force of electromagnetism, a non-universal interaction. Relying on this analogy it is shown that, although the geometric description of general relativity necessarily requires the existence of the equivalence principle, the teleparallel gauge approach remains a consistent theory for gravitation in its absence.
Keywords: gravitation; teleparallelism; equivalence principle